Problem-Based Learning To Enhance Pupils' Conceptual Understanding In Geometry - Herawati, Herawati; Sidik, Geri Syahril (Papanda Publisher, 2023)
This study investigated students' understanding of the concept through a pre-test and a post-test. Analysis of the pre-test showed that the initial abilities of students in the experimental and control groups were comparable, allowing for a fair comparison. Variations in students' ability to solve mathematical problems were investigated through post-test and N-gain data using different learning approaches. Two main hypotheses were proposed in this study: firstly, the experimental group would show a higher level of conceptual understanding than the control group; secondly, there would be a significant difference in improving students' conceptual understanding at different levels of ability. The analysis showed that the experimental group had a significantly higher level of conceptual understanding than the control group, which supported the first hypothesis. This finding indicates that the intervention positively affects students' conceptual understanding. In addition, the analysis results also showed a significant difference in the improvement of students' conceptual understanding with different proficiency levels, which supports the second hypothesis. These findings highlight the importance of learning approaches tailored to student's needs and abilities. This study provides strong evidence that specific mathematics learning models and initial mathematics ability contribute to improving students' conceptual understanding. These findings highlight the importance of tailored learning approaches to maximize students' mathematical concept understanding. The findings have valuable implications for educators and curriculum developers to develop more effective teaching strategies according to students' needs.